Lhx6 and Lhx8 promote palate development through negative regulation of a cell cycle inhibitor gene, p57Kip2. (12th June 2015) - Cesario, Jeffry M.; Landin Malt, Andre; Deacon, Lindsay J.; Sandberg, Magnus; Vogt, Daniel; Tang, Zuojian; Zhao, Yangu; Brown, Stuart; Rubenstein, John L.; Jeong, Juhee
Abstract : Cleft palate is a common birth defect in humans. Therefore, understanding the molecular genetics of palate development is important from both scientific and medical perspectives. Lhx6 and Lhx8 encode LIM homeodomain transcription factors, and inactivation of both genes in mice resulted in profound craniofacial defects including cleft secondary palate. The initial outgrowth of the palate was severely impaired in the mutant embryos, due to decreased cell proliferation. Through genome-wide transcriptional profiling, we discovered that p57 Kip2 ( Cdkn1c ), encoding a cell cycle inhibitor, was up-regulated in the prospective palate of Lhx6 −/− ;Lhx8 −/− mutants. p57 Kip2 has been linked to Beckwith–Wiedemann syndrome and IMAGe syndrome in humans, which are developmental disorders with increased incidents of palate defects among the patients. To determine the molecular mechanism underlying the regulation of p57 Kip2 by the Lhx genes, we combined chromatin immunoprecipitation, in silico search for transcription factor-binding motifs, and in vitro reporter assays with putative cis-regulatory elements. The results of these experiments indicated that LHX6 and LHX8 regulated p57 Kip2 via both direct and indirect mechanisms, with the latter mediated by Forkhead box (FOX) family transcription factors. Together, our findings uncovered a novel connection between the initiation of palate development and a cell cycle inhibitor via LHX. We propose a model in which Lhx6 and Lhx8 negatively regulate p57 Kip2 expression in the prospective palate area to allow adequate levels of cell proliferation and thereby promote normal palate development. This is the first report elucidating a molecular genetic pathway downstream of Lhx in palate development.